Pengembangan Sistem Monitoring Listrik Pada Ruangan Menggunakan NodeMCU dan MQTT - Arief Kurniawan; Dahnial Syauqy; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Electricity is major requirement in today's society. As an important source of energy for household, industrial even government. The increasing demand of electricity itself caused waste of energy. The energy use can be monitored by Kwh meter, to determine how much elecrity that has been used in room is not yet possible. Electricity monitoring usage system in the room using NodeMcu and MQTT (Message Queueing Telemetry Transport) would be a right solution. NodeMcu microcontroller as MQTT client publisher is using C++ program and using PubSubClient library. Then we perform a test to measure system performance of each node for monitoring electricty used in the room. There is a different value of amphere when we conduct the test that is 0-03 ampere when there is no electronic devices activity and 0.17 ampere when there is an activity of electronic device. It is possible to send the data using mqtt and the results can be displayed in grapchical form. At each node 1, 2, and 3 the diffrence is 1.50463 - 6.92544 watt-hour when the hair conditioner at level 1, iron and laptop is on, 1.4475-4.3209 watt-hour when the hair dryer at level 2, iron, and laptop is on and 0.094254-2.981733 watt-hour when all of the electronic devices is off.